The Time-Varying Variation Characteristics of Methane during Nitrogen Injection Process: An Experimental Study on Bituminous Coals - Aoxiang Zhang; Longyong Shu; Zhonggang Huo; Xin Song (Geofluids)
The existing research on CH4 displacement by N2 mainly focuses on the gas injection displacement mechanism and the factors affecting displacement efficiency. And most of them are theoretical analyses at the model level or multifactor analyses at the simulation test level, while there are few targeted physical simulation tests and quantitative analyses. Given the above problems, the experiment system was used to study the gas migration evolution law and time-varying characteristics of CH4 displacement by N2 in coal under different injection pressures. The experimental results show that the whole process of CH4 displacement by N2 can be divided into three stages: stage I (original equilibrium stage); stage II (dynamic balance stage); stage III (new equilibrium stage). The concentration of CH4 and N2 presents an opposite variation trend, and the variation rate of CH4 and N2 increased first and then decreased. The breakthrough time was 50 minutes, 45 minutes, 35 minutes, 25 minutes, and 20 minutes, respectively, under different injection pressures. The displacement efficiency increased with the injection pressures, while the replacement ratio decreased with the injection pressures. The maximum flow rate of CH4 was 0.085 mL/min, 0.110 mL/min, 0.130 mL/min, 0.222 mL/min, and 0.273 mL/min, respectively, under different injection pressures. The accumulated production of CH4 was 3.59 mL, 3.91 mL, 4.39 mL, 5.58 mL, and 5.94 mL, respectively, under different injection pressures. The effective injection pressure range was 1.6~2 MPa. This research can provide a reference for the theoretical research of N2-ECBM-related technology in low permeability reservoirs and the selection of injection pressure in the field technology implementation.